The War For Southern Minds: The Battles For Lost Cause History Books In North Carolina Schools - Melville, Auston (East Carolina University, 2023)
The United Daughters of the Confederacy set about to enshrine the ideology of the Lost Cause in the school literature of the South. Due to political upheaval in the 1890s, the Daughters had an extraordinary foundation upon which to begin their work. Throughout the following decades the Daughters fought to keep literature antithetical to their position out of schools. However, during this same time the Division had several factors hindering their work such as a reduction in numbers and a split focus. This thesis examines the beginning of the Daughters' power, major victories, and traces their decline in the literary war from the period of 1890-1976.
Keywords: UDC; Muzzey; United Daughters of the Confederacy--History; Lost Cause mythology; Textbooks--Censorship--United States; United States--History--Civil War, 1861-1865--Influence